What works in the classroom? promoting literacy practices in English - Ambigapathy Pandian (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2006)
Today, learners study and connect with one another across classrooms, community and country borders in new and exciting ways. The growth of global languages, specifically the worldwide spread of the English language in social, workplace and everyday communication demands radical transformation in the classroom. The first part of the paper presents some key findings of English literacy practices. The discussion gives a rather disturbing picture that literacy is still learnt as a set of skills and not as a social practice connected to various domains and comunities of practices in the real world. The second part of the paper unveils the recent shifts in thinking about literacy in general and specifically about learning in the English Language. The paper advances the Multiliteracies approach as propounded by the New London Group (1996) as a possible pathway of engaging the real world. This approach is supported by sample activities that motivate students to connect learning in real and meaningful ways.